Cyanidin-3-galactoside from Aronia melanocarpa ameliorates PM10 induced pulmonary injury by modulating M1/M2 macrophage polarization and NRF2/Sirt1 MAPK signaling. (March 2021) - Cui, Yanmin; Lin, Yang; Meng, Xianjun; Ma, Jingxuan; Deng, Haotian; Liu, Xia; He, Xinyuan; Zhao, Jin
Graphical abstract: Highlights: C3G, the most abundant anthocyanin in A. melanocarpa, has beneficial health effects. C3G ameliorated PM10-induced pulmonary injury in mice. C3G alleviated pulmonary inflammation, regulated macrophage polarization, and downregulated oxidative stress levels. The mechanism involves the NRF2/Sirt1, MAPK, and NF-κB signaling pathways. Abstract: Aronia melanocarpa is rich in anthocyanins that exert many beneficial effects. We extracted cyanidin-3-galactoside (C3G), the most abundant anthocyanin in Aronia melanocarpa, and applied to PM10-exposed mice to investigate anti-inflammatory properties and underlying cellular mechanism. Administration of C3G ameliorated PM10-induced pulmonary inflammation by reducing recruitment of macrophages and pro-inflammatory cytokine mRNA levels in lung tissues. C3G also regulated M1 and M2 macrophage balance. An in vitro demonstrated that C3G decreased M1 macrophage markers, while increased M2 macrophage markers. The secretion of pro-inflammatory cytokines was reduced as well. Study of the cellular mechanism revealed that C3G inhibited mitogen-activated protein kinase and the translocation of nuclear factor-κB in to nuclei. C3G treatment also downregulated expression of reactive oxygen species, nuclear factor (erythroid-derived 2)-like 2, and silent information regulator protein 1 in macrophages. These findings highlight the potential use of C3G as a functional food to prevent the development of PM10-induced pulmonary injury.